Improvement of interlocking thin sheet metal in joining using plastic deformation process - Mohd Nor Fikry, Jamaludin (2016)
The automobile industry, in particular, uses clinching in certain parts of the vehicle body. Clinching is also used in furniture and computer industries, in different kind household appliances as well as in ventilation and air conditioning products. Clinching is the mechanical clamping methods to join sheet metal without extra components, which use the special tools to form a mechanical interlock between the sheets metal. Normally, the tools of mechanical clinching are a punch and a die. The first procedure to carry out this research is by design the suitable punch and die shape in joining two sheet metals. All the parameters that involve in fabricating the punch and die shape such as the diameter of die, the diameter of punch, punch stroke, die depth and the thickness of the sheet, the point that must be emphasis. This all factors are related to each other. If the parameters are not suitable, it may cause the interlocking between two sheets will not happen. Thus, no joining process are occur. For the die diameter, it must consider the size of punch diameter and also the thickness of sheet metal for in being fabricate. This is because if it too large or too small, it may cause the defect to occur which are button separation mode for the large size of die diameter and neck fracture for the small size of die diameter. Meanwhile, for the punch stroke, it must consider the die depth and also the thickness of the sheet metal. If the small punch stroke are apply at thick sheet metal and small die depth, it may cause the joining between the two sheets will not occur. Hence, die depth and the thickness of the sheet metal should be emphasized before deciding the punch stroke to ensure the interlocking will occur.